Biocides and Novel Antimicrobial Agents for the Mitigation of Coronaviruses - Dev Kumar, Govindaraj; Mishra, Abhinav; Dunn, Laurel; Townsend, Anna; Oguadinma, Ikechukwu Chukwuma; Bright, Kelly R.; Gerba, Charles P. (Frontiers in Microbiology, 2020)
In December, 2019, a highly infectious and rapidly spreading new pneumonia of unknown cause was reported to the Chinese WHO Country Office. A cluster of these cases had appeared in Wuhan, a city in the Hubei Province of China. These infections were found to be caused by a new coronavirus which was given the name “2019 novel coronavirus” (2019-nCoV). It was later renamed “severe acute respiratory syndrome coronavirus 2,” or SARS-CoV-2 by the International Committee on Taxonomy of Viruses on February 11, 2020. It was named SARS-CoV-2 due to its close genetic similarity to the coronavirus which caused the SARS outbreak in 2002 (SARS-CoV-1). The aim of this review is to provide information, primarily to the food industry, regarding a range of biocides effective in eliminating or reducing the presence of coronaviruses from fomites, skin, oral/nasal mucosa, air, and food contact surfaces. As several EPA approved sanitizers against SARS-CoV-2 are commonly used by food processors, these compounds are primarily discussed as much of the industry already has them on site and is familiar with their application and use. Specifically, we focused on the effects of alcohols, povidone iodine, quaternary ammonium compounds, hydrogen peroxide, sodium hypochlorite (NaOCl), peroxyacetic acid (PAA), chlorine dioxide, ozone, ultraviolet light, metals, and plant-based antimicrobials. This review highlights the differences in the resistance or susceptibility of different strains of coronaviruses, or similar viruses, to these antimicrobial agents.